Modification of postmortem wounds by Dermestes maculatus (Coleoptera: Dermestidae) activity: A preliminary study - Zanetti, Noelia Inés (2015)
The purpose of this analysis was to evaluate the effects of insect activity on hacking trauma which was inflicted with a small cleaver and a razor blade under controlled conditions. Three pig hooves were each subjected to a blow with a small cleaver and a cut with a razor blade prior to insect exposure. We used Dermestes maculatus DeGeer 1774 species. These beetles made principally depressions and destruction on both wounds, and bites were observed on the edges of the wounds. As time passed and insects fed and refuge, chop marks were deformed and disappeared, taking this less than a month. Thus, D. maculatus could mask postmortem wounds and probably premortem wounds, and so the cause of death.